An Overview of the Green Internet of Things (IoT) (International Journal of Innovative Research in Computer Science & Technology, 2021)
In line of the huge scope of the digital  context, the number of subscribers of digital services, and the  number of digital devices, levels of energy intake have reached alarming levels during the last decade. By 2020, the  number of linked devices will have augmented almost to  forty nine billion, and in the coming years almost by 2030, it  will have increased to 100 billion. As a result, experts  anticipate a massive increase in content size and data usage rate (hundreds of thousand times larger in coming decade than it was in past two decades) at the cost of extreme carbon  emissions into the atmosphere. As the Internet of Things  (IoT) connects everything in the smart world, energy usage is an issue and a promising study field. A green IoT is  proposed in order to achieve a low power consumption IoT.  The purpose of this article is to offer an overview of green  IoT. It also goes through the green IoT life cycle, which  includes green design, green manufacture, green use, and  green recycling. Green IoT technologies are also explored,  such as green tags, green sensor networks, and green internet  technologies. In addition, there are studies on IoT using fifth  gen technologies and IoT for smart metropolises. Finally,  future research topics as well as outstanding issues in the  field of green IoT are discussed.
Keywords: 5G; Cloud Computing; Energy Efficiency; Green IoT; Internet of Things (IoT); Smart Cities; Wireless Sensor Networks